Assessment of the New Nanocomposites (PMMA/(HAP, FE2O3) + CROCUS SATIVUS L.) as Dental Fillings and Antifungal. - Ali Hammed, Dhulfiqar; Hadi Shinen, Mohammed; Ibrahim Obayes, Abbas (Hammurabi Journal of Medical Sciences, 2024)
Background: Polymethyl methacrylate (PMMA) is a cost-effective polymer that exhibits unique properties when combined with organic nanoparticles to create polymer composites with enhanced functionality. Objectives: This study seeks to examine the surface roughness of dental fillings constructed from biomaterials using polymethylmethacrylate polymer, and to assess the varying patterns of salivary pH and salivary amylase activity. Material and Methods: nanohydroxyapatite prepared from fish bone waste, Fe2O3, and polymethyl methacrylate with the addition of prepared saffron dye was utilized. The proportion of nanohydroxyapatite and iron oxide added was (0.2, 0.4, 0.6) g. The casting method was used to create membranes for the prepared fillings, which were used to investigate the surface roughness. Standardized protocols were to evaluate the pH level and amylase activity using the colorimetric method. Results: The surface roughness of Fe₂O₃ nanofillers was noticeably greater than the surface roughness of HAP nanofillers. Although the roughness values varied, they were still below 200 nm. This variation is directly related to the size, diameter, thickness, and relative volumetric loading capacity of the nanomaterials. Salivary alpha-amylase and pH were chosen as biomarkers for changes in the new filling, reflecting the activity of the immune system. The activity was measured in three cases: first, without saliva treatment, and second, when saliva was treated with the addition of different concentrations (0.7%, 8%, 1 g). The results confirmed that the materials used do not affect the activity of saliva enzymes and pH conditions, indicating that the saffron-colored nanomaterials, HAP and Fe2O3, are biocompatible. At (0.6g) of nano-Fe2O3, antifungal activity against Candida albicans was detected. According to the study, saffron-dyed nano-Fe2O3 improve the strength and longevity of composites, and at a concentration of 0.6g, the composite demonstrated antifungal activity against Candida albicans. Conclusion: The surfaces of the prepared fillings are smooth crystalline surfaces and non-toxic and biodegradable fillings made of hydroxyapatite, iron oxide and saffron dye based on (PMMA) indicating their efficacy in dental restoration as well as pH and amylase levels in the filling remained stable. It possesses antifungal properties.